Oral health of centenarians and supercentenarians - Frese, Cornelia; Zenthöfer, Andreas; Aurin, Kerstin; Schoilew, Kyrill; Wohlrab, Theresa Friederike; Sekundo, Caroline (Journal of oral science, 2020)
There are many studies on the homebound and institutionalized elderly; however, few studies focus on centenarians and supercentenarians, i.e., people aged 100 and 110 years, respectively. Due to the demographic changes, the population of centenarians is set to increase more than that of other age groups. Therefore, this article aims to review the available literature regarding how oral health might display in this age group and highlight aspects necessitating further research. Oral health, oral healthrelated quality of life, saliva, and the oral microbiome were emphasized in this study. Most papers relevant to the research questions were excluded because the mean age of participants was <100 years. Only two papers were found on centenarians’ oral health status and saliva and no studies were found focusing on the oral health-related quality of life or oral microbiome. The reviewed studies demonstrate that centenarians presented with good oral mucosal conditions, dental conditions, and general health. The present literature is insufficient to come to a definite conclusion regarding how aging affects the oral health of centenarians and supercentenarians. The limited available research indicates that centenarians display better oral health than other individuals in their respective birth cohorts.